APLIKASI OBJEK WISATA 3D AUGMENTED REALITY BERBASIS MOBILE: Aplikasi Objek Wisata 3D Augmented Reality Berbasis Mobile - Yoyon Efendi; Agung Marinda; Lusiana Lusiana (Jurnal Mantik, 2019)
Riau Province has various natural attractions such as Siak Palace, Sang Nila Utama Museum and Muara Takus Temple. At the Siak Palace, currently the information obtained is only in the form of websites and brochures. But information is not enough, a tourist attraction will be more interesting if the public can see and get the tour object directly. Then technology is needed that can be enjoyed by visitors through cellular media such as Augmented Reality. Making begins with collecting Riau tourism data that will be made as a model using software sketches. Then it is processed again using Unity by using markerless using Vuforia. The features in this application display some detailed information on the Siak 3D Palace. With the existence of mobile-based Augmented Reality technology, it is easier for people who want to travel to see buildings and historical objects at the Siak Palace.